Exploring Barriers in Self-Reporting of Errors and Near Misses: A Cross-Sectional Study on Radiation Oncology in Saudi Arabia - Alahmad H; Alshahrani AM; Alenazi K; Alarifi M; Abanomy A; Alhulail AA; Albathi RA; Alzughaibi S; Almanaa M (Journal of Multidisciplinary Healthcare, 2024)
Haitham Alahmad,1 Abdulrhman M Alshahrani,2 Khaled Alenazi,1 Mohammad Alarifi,1 Ahmad Abanomy,1 Ahmad A Alhulail,3 Raed A Albathi,4 Saleh Alzughaibi,5 Mansour Almanaa1 1Department of Radiological Sciences, College of Applied Medical Sciences, King Saud University, Riyadh, 4545, Saudi Arabia; 2Radiology Technology Department, College of Applied Medical Sciences, Qassim University, Buraydah, Saudi Arabia; 3Department of Radiology and Medical Imaging, Prince Sattam Bin Abdulaziz University, Al-Kharj, 16278, Saudi Arabia; 4Radiology Department, Prince Sultan Military Medical City, Riyadh, Saudi Arabia; 5Health Informatics Department, College of Health Science, Saudi Electronic University, Riyadh, Saudi ArabiaCorrespondence: Haitham Alahmad, Department of Radiological Sciences, College of Applied Medical Sciences, King Saud University, P.O. Box 145111, Riyadh, 4545, Saudi Arabia, Tel +966114693567, Email hnalahmad@ksu.edu.saBackground: Radiation therapy utilizes complex technologies to target tumors. Radiation therapy is not immune to human errors. Reporting medical errors and near misses is crucial to improving patient outcomes and ensuring the safety of future patients.Objective: This study aimed to measure the attitudes of radiotherapy staff members in Saudi Arabia regarding reporting errors and near misses in radiation therapy practice. It also examined the participants’ reporting patterns and behaviors and explored the potential barriers to reporting errors and near misses as perceived by the participants.Methods: A cross-sectional study utilizing an online questionnaire was implemented. A sample of 70 health professionals working in radiation oncology departments in Saudi Arabia, including radiation oncologists, medical physicists, and radiotherapists, were recruited to participate in this study from January to June 2023. The data was analyzed using chi-squared testing to compare different groups, and the Kruskal–Wallis was used to find any statistically significant differences between different groups.Results: The study included 70 radiotherapy staff members. Professional roles did not significantly impact participants’ decisions to report minor or major errors, with most consistently reporting errors to their supervisors regardless of role. The study revealed that fear of professional sanctions and the potential negative impact on a department’s reputation are significant barriers to reporting errors or near misses. However, Only 17% of radiation oncologists did consider departmental sanctions as a barrier. Participants identified communication failure as the most significant source of errors in radiation oncology departments. The study also found a high level of agreement among the participants regarding the responsibility of reporting errors and near misses.Conclusion: The study investigated reporting errors and near misses in radiotherapy and considered the factors influencing them. The findings highlight the importance of effective communication and the implementation of an electronic reporting system.Keywords: radiotherapy, radiation oncology, medical errors, near misses